New understanding of microbial growth cycle for efficient waste-activated sludge disposal by preserving microbial self-degradation activity during the decline phase - Xiqi Li; Aijie Wang; Zhe Yu; Hualin Wang; Hengzhi You; Jifei Xu; Jingyu Zhang; Wenzong Liu (Water Research X)
Diverse pretreatment methods have been developed for cell-cracking and sludge denaturation to harvest pretreated sludge as the suitable fermentation substrate, but new inoculation is not always working quickly or adaptively for the pretreated sludge. This study established a sludge SDMP method by integrating RL and HSHC to fully use the enriched microorganisms with decomposing enzymes/abilities at the sludge decline phase for organic matters bioconversion. The SDMP method cracked EPS but preserved and enhanced the microbial viability and the activity of enzymes related to hydrolysis and acidifying. Then the VFAs production cycle of SDMP sludge was shortened by 36.25 % than alkaline pretreated sludge, and the yield reached 4482.19 mg COD/L in 3 days with the organic matter conversion rate of 369.36 mg COD/g VSS. Preserved and enriched sludge self-degradation microorganisms composed a critical part of the dominant community, including Mycobacterium, norank_f__Pirellulaceae, IMCC26207, norank_f__JG30-KF-CM45, and Petrimonas. The interaction network centered on them facilitated acidogenic metabolism by reinforcing pathways such as glycolysis, pyruvate metabolism, and the Stickland reaction in amino acid metabolism. This study provides new insights into developing microbial functions for recycling resources from sludge.